2018
DOI: 10.1007/s00259-018-4143-8
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment PET/CT imaging of angiogenesis based on 18F-RGD tracer uptake may predict antiangiogenic response

Abstract: F-RGD uptake on PET/CT imaging pretreatment may predict the response to antiangiogenic therapy, with higher F-RGD uptake in tumors predicting a better response to apatinib therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 25 publications
1
19
2
Order By: Relevance
“…Our quanti cation of immunohistochemical staining in primary tumor showed that the expression of VEGF and Ki67 in LoVo tissues were stronger than LS174T ones, combined with the results of correlation analysis, a weak correlation between 18 F-RGD SUVmean ratio and Ki67 expression (P = 0.0438) and a strongly signi cant correlation between RGD SUVmax ratio/SUVmean ratio and VEGF expression in primary tumor (P = 0.001 and P 0.0001, respectively), indicating that the SUVmax ratio/SUVmean ratio of 18 F-RGD may be recognized as an ideal radiation maker to re ect tumor angiogenesis in CLM mice model. Our viewpoint was consistent with previous reviews, that 18 F-RGD is a promising tracer for tumor angiogenesis imaging and monitoring anti-angiogenesis therapy in solid tumor [25,26]. In Sibel lsal's study, they also veri ed that the expression of integrin αvβ3, which are targeted by RGD-based peptides tracer, was associated with cell proliferation in glioblastoma [27].…”
Section: Discussionsupporting
confidence: 91%
“…Our quanti cation of immunohistochemical staining in primary tumor showed that the expression of VEGF and Ki67 in LoVo tissues were stronger than LS174T ones, combined with the results of correlation analysis, a weak correlation between 18 F-RGD SUVmean ratio and Ki67 expression (P = 0.0438) and a strongly signi cant correlation between RGD SUVmax ratio/SUVmean ratio and VEGF expression in primary tumor (P = 0.001 and P 0.0001, respectively), indicating that the SUVmax ratio/SUVmean ratio of 18 F-RGD may be recognized as an ideal radiation maker to re ect tumor angiogenesis in CLM mice model. Our viewpoint was consistent with previous reviews, that 18 F-RGD is a promising tracer for tumor angiogenesis imaging and monitoring anti-angiogenesis therapy in solid tumor [25,26]. In Sibel lsal's study, they also veri ed that the expression of integrin αvβ3, which are targeted by RGD-based peptides tracer, was associated with cell proliferation in glioblastoma [27].…”
Section: Discussionsupporting
confidence: 91%
“…Another study in 61 patients with esophageal squamous cell carcinoma found quite similar results but stated that alfatide I could still provide complementary molecular information about the metastasis of this cancer [198]. Recently, alfatide I PET imaging was shown to possibly be predictable of the response to antiangiogenic agent apatinib [199].…”
Section: Current Clinical Use Of [18f]alf-labeled Biomoleculesmentioning
confidence: 89%
“…At present, the targeted drugs for anti-angiogenesis therapy in breast cancer have been used in clinical research [19]. Imaging based on integrin α v β 3 found that 18 F-ALT-NOTA-PRGD 2 may predict a better response to apatinib anti-angiogenesis therapy in breast cancer [34]. A receptor imaging by combing diagnosis and monitoring drug response may be a valid instrument to select breast cancer patients who could bene t from targeted therapies [35].…”
Section: Discussionmentioning
confidence: 99%